A block sparse shared-memory multifrontal finite element solver for problems of structural mechanics - Fialko, S. Y. (Computer Assisted Methods in Engineering and Science, 2017)
The presented method is used in finite-element analysis software developed for multicore and multiprocessor shared-memory computers, or it can be used on single-processor personal computers under the operating systems Windows 2000, Windows XP, or Windows Vista, widely popular in small or mediumsized design offices. The method has the following peculiar features: it works with any ordering; it uses an object-oriented approach on which a dynamic, highly memory-efficient algorithm is based; it performs a block factoring in the frontal matrix that entails a high-performance arithmetic on each processor and ensures a good scalability in shared-memory systems. Many years of experience with this solver in the SCAD software system have shown the method's high efficiency and reliability with various large-scale problems of structural mechanics (hundreds of thousands to millions of equations).